University - Industry Relations: A Thrust for Transformation of Knowledge and Economic Acceleration - Lamichhane, Shreeram; Sharma, Tanka Nath (Journal of Education and Research, 2010)
The complex theory calls for probing a given context in a holistic manner because the isolationist approach is less likely to produce authentic knowledge of the reality. It is also important to perceive the nature of connectivities in all spheres of human existence. Once we put motion in our lives essentially we need to act with the understanding that there exist robust connections between human existence and numerous existence-related variables. This article attempts to dig out the inexorable connection between university and industry. Neither of these two constituents accumulates energy if left to function in isolation. Rather a mutual reinforcement between them is most likely to stimulate a powerful flow of synergy which will empower both of them to enjoy a win-win situation. To this end, a sharing modality between university and industry is what this article attempts to focus on. DOI: http://dx.doi.org/10.3126/jer.v2i0.7624 Journal of Education and Research Vol. 2, 2010 p.59-66